IMPLEMENTATION VALUE ENGINEERING FOR ARCHITECTURAL COST IN 6X10 AND 6X12 HOUSING RESIDENTIAL AREA (CASE STUDY: RESIDENTIAL AREA IN BINTARO JAYA) - Irfanto, Ryobi; Chiandy (Universitas Trisakti, 2025)
The issue of limited land in DKI Jakarta has resulted in a decrease in residential development, making it difficult for many residents to obtain proper housing. As one of the supporting cities of the capital, South Tangerang is favored by private developers for residential area development, particularly in the Bintaro Jaya area. The research is conducted on a housing project by PT. C, a private developer in Indonesia, focusing on houses with the highest number of units built, specifically type 6×10 and 6×12 houses. Value engineering needs to be carried out to achieve cost efficiency to determine the amount and percentage of cost savings. The research focuses only on architectural work because in housing project architectural works have a larger cost. The process begins with the information phase using a work breakdown structure, cost breakdown, and Pareto chart, followed by a function analysis phase using a function analysis index, a creative phase to find alternative materials, then an evaluation process, and finally presenting the results in the presentation phase. The research results for type 6×10 houses show savings of IDR 36,144,550.85 with a percentage of 10.68%, while type 6×12 houses show savings of IDR 41,508,819.29 with a percentage of 8.25%. The difference in percentage is due to the variation in work volume. The larger the work volume, the smaller the percentage of savings